Assessment of depression and internalized-stigma among adult asthma patients in Bangladesh: a cross-sectional study - Saquib Ahmed-Chowdhury; Sohail Ahmad; Md. Moklesur Rahman Sarker; Nahlah Elkudssiah Ismail (Springer, 2024)
Abstract Objective Suboptimal asthma control among patients is associated with psychosocial factors, including depression and stigma, hindering effective asthma management. This study aimed to assess depressive symptoms and internalized stigma among adult asthma patients while investigating their relationships with sociodemographic and asthma-related medical factors. Methods In this cross-sectional study, 325 adult asthma patients (aged > 18 years old) were recruited from the National Asthma Centre in Dhaka, Bangladesh, using a researcher-administered questionnaire and convenience sampling. The questionnaire included sections on sociodemographic characteristics, medical data, the 9-item Patient Health Questionnaire (PHQ-9) to assess depressive symptoms, and a 22-item stigma scale to assess internalized stigma. Data were analyzed using descriptive and inferential statistics. Results The majority of participants were aged 18-40 years (54.2%), male (53.5%), from rural areas (50.8%), with a monthly family income of < US$250 (55.1%), and diagnosed with asthma for > 5 years (46.5%). The mean PHQ-9 score was 7.36 (± 6), indicating mild depressive symptoms, and the internalized stigma score was 62.2 (± 10.26), indicating moderate internalized stigma. Depression and stigma varied significantly across several factors, including age, education, ED visits, hospitalizations for asthma, number of asthma medicines, home nebulizer use, PEF rate, BMI, comorbidities, and asthma symptom control (p < 0.05). Stigma was correlated with depression and negatively correlated with age and years since asthma diagnosis (p < 0.01). Conclusion This study highlights associations between depressive symptoms, internalized stigma, and various sociodemographic and medical factors among asthma patients. Notably, stigma was higher among younger adults and recently diagnosed patients. Effective interventions are needed to mitigate stigma and depression in this patient population.